Cardioprotective effects of sodium thiosulfate against doxorubicin-induced cardiotoxicity in male rats - Maryam Shekari; Narges Khalilian Gortany; Mina Khalilzadeh; Alireza Abdollahi; Homanaz Ghafari; Ahmad Reza Dehpour; Mahmoud Ghazi-Khansari (BMC, 2022)
Abstract Background Doxorubicin (DOX) is an effective antitumor agent, but its clinical usage is limited due to adverse cardiotoxic effects. Several compounds have been studied to reduce DOX cardiotoxicity to improve its therapeutic index. This study was aimed to investigate the protective effects of sodium thiosulfate (STS) pre-treatment against DOX-induced cardiomyopathy in rats. Methods Male Wistar rats were randomized into 4 groups: control (saline), DOX (2.5 mg/kg, 3 times per week, intraperitoneal [i.p.]), STS (300 mg/kg, 3 times per week, i.p), and DOX + STS (30 min prior to DOX injection, 3 times per week, i.p.) over a period of 2 weeks. The body weight, electrocardiography, histopathology, papillary muscle contractility, and oxidative stress biomarkers in heart tissues were assessed. Results The results indicated that STS significantly improved the body weight (P < 0.01), decreased QRS complex and QT interval on ECG (P < 0.05 and P < 0.001, respectively), as well as declined the papillary muscle excitation, and increased its contraction (P < 0.01) compared to DOX-treated rats. STS strongly suppressed oxidative stress induced by DOX through the significant improvement of the cardiac tissue antioxidant capacity by increasing glutathione, superoxide dismutase (P < 0.001), and decreasing the level of lipid peroxidation (P < 0.01). Conclusion Taken together, the results of this study demonstrated that STS showed potent cardioprotective effects against DOX-induced cardiotoxicity by suppressing oxidative stress.